How Decision Makers Evaluate Alternatives and the Influence of Complexity - Nutt, Paul C. (Management Science, 1998)
The evaluation of alternatives during organizational decision making was investigated to uncover evaluation tactics used by decision makers and how these tactics and complexity influenced success. Evaluation tactics that relied upon subjective, judgmental, bargaining, and analytical inferences were uncovered from 317 strategic decisions. The complexity of these decisions was measured by the numbers of alternatives considered, number of criteria used, and perceived difficulty of the evaluation task to identify conditions under which the evaluation tactics were successful. The managerial implications of evaluating alternatives with the tactics that used judgmental, bargaining, analytical, and subjective inferences under different levels of complexity are discussed.